1994
DOI: 10.1128/jvi.68.12.7966-7973.1994
|View full text |Cite
|
Sign up to set email alerts
|

Entry and release of transmissible gastroenteritis coronavirus are restricted to apical surfaces of polarized epithelial cells

Abstract: The transmissible gastroenteritis coronavirus (TGEV) infects the epithelial cells of the intestinal tract of pigs, resulting in a high mortality rate in piglets. This study shows the interaction of TGEV with a porcine epithelial cell line. To determine the site of viral entry, LLC-PK1 cells were grown on permeable filter supports and infected with TGEV from the apical or basolateral side. Initially after plating, the virus was found to enter the cells from both sides. During further development of cell polarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
34
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 40 publications
9
34
0
2
Order By: Relevance
“…2 and 3) indicated that TGEV can replicate in several organs in pigs, but they mainly distribute in swine small intestine, for the amino peptidase N (APN), a TGEV major receptor in pigs, is abundantly expressed in the apical membrane of the small intestine epithelial cells, and which has a bigger quantity and higher activity in small intestine than other organs. Through the APN most of infectious TGEV invade host small intestine epithelial cells and initiate viral replication (Delmas et al, 1992;Rossen et al, 1994;Weingartl and Derbyshire, 1994). In our study, after the plasmids injected into mini-pigs via the precava, the reporter gene EGFP expressed abundantly in small intestine cells (data not shown).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…2 and 3) indicated that TGEV can replicate in several organs in pigs, but they mainly distribute in swine small intestine, for the amino peptidase N (APN), a TGEV major receptor in pigs, is abundantly expressed in the apical membrane of the small intestine epithelial cells, and which has a bigger quantity and higher activity in small intestine than other organs. Through the APN most of infectious TGEV invade host small intestine epithelial cells and initiate viral replication (Delmas et al, 1992;Rossen et al, 1994;Weingartl and Derbyshire, 1994). In our study, after the plasmids injected into mini-pigs via the precava, the reporter gene EGFP expressed abundantly in small intestine cells (data not shown).…”
Section: Discussionmentioning
confidence: 61%
“…It indicated that the plasmids were efficiently delivered into small intestine cells, the target of TGEV, by the method of precava injection. This may be a major reason why a small dose of shRNA-expressing plasmids (3 mg/piglet) could well protect mini-pigs from clinical symptoms and histopathology induced by TGEV infection (Delmas et al, 1992;Rossen et al, 1994;Weingartl and Derbyshire, 1995). The data also suggested that precava injection may be a good choice for treating animals with intestinal diseases as this route uses relatively short distance to reach small intestine from the precava.…”
Section: Discussionmentioning
confidence: 97%
“…Porcine enteric coronaviruses replicate in IECs and are transmitted via a fecal-oral route. The viral entry and release for TGEV are restricted to the apical surface of polarized epithelial cells (Rossen et al, 1994). Experimental infection of newborn piglets with TGEV induces a strong and early IFN-␣ production in serum and intestinal secretions (La Bonnardiere and Laude, 1981).…”
Section: Activation Of Ifn-˛/ˇ By Tgevmentioning
confidence: 99%
“…2006; Cong and Ren, 2014). Epithelial cells grow with a polarized topology that involves the separation of the plasma membrane into apical and basolateral domains (Rossen et al, 1994;Cong and Ren, 2014). It has been demonstrated that the entry and release of several coronaviruses in polarized epithelial cells is restricted to the apical plasma membrane, e.g.…”
Section: Introductionmentioning
confidence: 99%